Thermal stratification suppression in reduced or zero boil-off hydrogen tank by self-spinning spray bar. (26th July 2019) - Zuo, Z.Q.; Sun, P.J.; Jiang, W.B.; Qin, X.J.; Li, P.; Huang, Y.H.
Abstract: Thermal stratification of cryogenic propellants under the condition of external heat leakage is a dominating factor pressurizing the storage tank, which hinders long-term on-orbit storage missions for future explorations. Whether a thermodynamic venting system or cryocooler is introduced to reduce the boil-off losses or even realize zero boil-off of the cryogens, an efficient mixing and heat-exchanging device is a prerequisite for eliminating thermal stratification. Usually, a subcooled stream is introduced, which is injected into the tank through the nozzles on a spray bar. Early research provided evidence that the cooling effect is related to the arrangement of the nozzles. In contrast to adopting a heavy plate spray bar to realize the temperature profile symmetry along the tank axis, this study proposes an assembly with a rotatable nozzle head to diminish the temperature non-uniformity in the tank. In this manner, over 70% of the spray bar payload can be saved compared to the plate configuration. A three-dimensional model was established to investigate the temperature distribution of liquid hydrogen at zero gravity in a tank containing such a rotatable sprayer, which was passively driven by the counterforce of the injection flow, and therefore excluded an extra power drive demand. The injection inlet velocity, as well as the length and quantity of the nozzle arms, were analyzed parametrically to optimize the destratification performance. By employing the self-spinning sprayer, the standard deviation of the temperature in the tank could be lowered, along with the benefits of a significant payload reduction and elimination of direct power input. Highlights: A rotatable spray bar is proposed to destratify the liquid hydrogen in on-orbit propellant tank. 6DOF model is integrated into the computational model to simulate the mixing process. By using the rotatable spray bar, temperature uniformity is improved, with reduction in payload.